The educational integration of separated minors: a comparison of the situations in France and Quebec - Lemaire,Eva (2014)
This article proposes to investigate the educational experiences of thirty-two separated children (unaccompanied minors seeking refuge) in two different regions: the Ile-de-France (Paris) region of France and the province of Quebec in Canada. It allow for a better understanding of the role and the actual place that education has in the integration process of these vulnerable young migrants.